IMPROVEMENT OF ESTROGEN DEFICIENCY TREATMENT AND PREVENTION OF METABOLIC DISORDERS IN PERIMENOPAUSAL WOMEN AFTER OOPHORECTOMY - Shukurova M.R., Irgasheva S.U. (Central Asian Journal of Medicine, 2025)
Background:Surgical menopause resulting from bilateral oophorectomy in perimenopausal women leads to an abrupt estrogen deficiency, significantly impacting quality of life and increasing the risk of metabolic, cardiovascular, and psychoemotional disturbances. Hormone replacement therapy (HRT) is considered an effective intervention to alleviate these consequences. Objective:To evaluate the clinical, metabolic, hormonal, cognitive, and quality-of-life outcomes in perimenopausal women following surgical menopause, comparing those receiving HRT to those not undergoing hormone therapy. Methods:This prospective study included 78 perimenopausal women aged 40–55 years who underwent bilateral oophorectomy for various medical indications. Participants were randomly divided into two groups: HRT group (n = 40) and non-HRT group (n = 38). Clinical symptoms, bone mineral density (T-score), lipid profile, cognitive function, hormonal status, and quality-of-life measures (MRS, PSQI, HADS, FSFI, MENQOL) were assessed at baseline and at 3, 6, and 12 months post-surgery. Results:Patients in the non-HRT group exhibited more severe climacteric symptoms, a greater decline in bone mineral density, unfavorable lipid profiles, more frequent cognitive impairment, and lower quality-of-life scores. HRT significantly improved vasomotor and psychoemotional symptoms, preserved bone health, stabilized hormonal levels, reduced metabolic risks, and enhanced sexual function and well-being. Younger patients (<45 years) were more vulnerable to early deterioration, yet responded better to timely HRT. Conclusions:HRT substantially mitigates the adverse effects of surgical menopause in perimenopausal women. A multidisciplinary, individualized approach is critical to managing estrogen deficiency and improving long-term outcomes. Further studies are required to optimize HRT protocols and confirm long-term benefits.